Tinjauan Yuridis Pemberian Cover Asuransi DalamPerjanjian Kredit Di Pt. Bank Rakyat Indonesia(Persero) Cabang Boyolali - Ningsih, Isna Fitriana (2016)
This study aims to determine the procedures for granting credit insurance cover insurance as proposed by the customer debtor and form the legal protection of the rights and obligations accepted by the customer if it has approved the proposed credit agreement by Bank Rakyat Indonesia (BRI). This research used juridical empirical approach using a type of primary data and secondary data. Data collection techniques using literature study, documentation, and interviews, then analyzed by qualitative analysis. The results show the procedure of the insurance as credit guarantees that cover the customer must first be bound by the credit agreement, with the dependent customers in a credit agreement, it is automatically part of the Bank has insured. Regarding legal protection is acceptable if a clause in the loan agreement is not in accordance with Article 18 paragraph (1) of Law No. 8 of 1999 on Consumer Protection, basically the customers who have ever received a credit facility that covered insurance are satisfied with legal protection.